1983
DOI: 10.1029/ja088ia11p08643
|View full text |Cite
|
Sign up to set email alerts
|

Voyager photopolarimeter stellar occultation of Saturn's rings

Abstract: On August 25, 1981, the Voyager 2 photopolarimeter system observed a stellar occultation by Saturn's rings. We present a brief description of this experiment along with details of the data reduction. The occultation results are given in tabular and graphical form at a resolution of 60 km. Histograms of the frequency of optical depth show dominantly unimodal distributions in each of the classical ring elements. The frequency distribution of the entire ring system shows three modes at τ ≈ 0.08, τ ≈ 0.5, and τ ≳ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
1

Year Published

1986
1986
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(32 citation statements)
references
References 3 publications
1
30
0
1
Order By: Relevance
“…2 The radius scale of the PDS file was that determined by Nicholson et al (1990), which differs by <2 km from the French et al (1993) radius scale, so no further geometric corrections were made. The 1σ sensitivity level of the averaged PPS data, taking into account the average background count rate (Esposito et al 1983b), corresponds to a normal optical depth τ max = 2.6.…”
Section: Pps Datamentioning
confidence: 99%
See 1 more Smart Citation
“…2 The radius scale of the PDS file was that determined by Nicholson et al (1990), which differs by <2 km from the French et al (1993) radius scale, so no further geometric corrections were made. The 1σ sensitivity level of the averaged PPS data, taking into account the average background count rate (Esposito et al 1983b), corresponds to a normal optical depth τ max = 2.6.…”
Section: Pps Datamentioning
confidence: 99%
“…Most of our quantitative knowledge of the optical depths and detailed radial structure in the ring system, however, is derived from occultation experiments carried out by the same spacecraft. These include occultations of the star δ Sco observed by the Voyager 2 Ultraviolet Spectrometer (UVS) (Sandel et al 1982 and Photopolarimeter Subsystem (PPS) (Esposito et al 1983b(Esposito et al , 1987, at effective wavelengths of 0.11 and 0.27 µm, respectively, as well as a dual-frequency radio occultation experiment at 3.6 and 13 cm carried out with the Voyager 1 Radio Science Subsystem (RSS) . The sampling resolutions of the PPS and UVS data are 0.10 and 3.2 km, respectively, while the RSS data for the A and C rings have been diffraction-corrected to effective radial resolutions of 1 and 5 km ).…”
Section: Introductionmentioning
confidence: 99%
“…There are sharp gravitational resonance peaks identified by Holberg, and two other peaks, at R/R = 1.311 and 1.658, which, to judge from w their appearance, are probably due to resonances. Further, there is a remarkable eccentric ring at 1.45, which has been studied in detail by Esposito et al (1983), but has not been identified. Moreover, there are a large number of well-defined maxima, which clearly differ from the resonance peaks; they have flat tops and constitute rectangles with steep sides.…”
Section: The C Ringmentioning
confidence: 99%
“…Peak at R/R = 1.449 3 Inside the region of shadows produced by the Shepherds but outside the antishadows produced by the holes in the A ring there is a very strong peak at R/R S = 1.449. A detailed analysis by Esposito et al (1983) has shown that this constitutes an eccentric ringlet. Although there are other eccentric ringlets, this is unique due to its strong eccentricity.…”
Section: Shadows Of the A Ring (Inside R/r = 1 45) : Antishadowsmentioning
confidence: 99%
“…However, there seem to be only few attempts to analyse the data obtained by the various missions towards an understanding of the dynamics of these systems. In this paper, we propose to apply the recently developed theory of deterministic chaos (Schuster 1984) to the data acquired by the Voyager missions (photopolarimeter recordings; Esposito et al, 1983). It may be mentio.ned that a study in the framework of deterministic chaos is relevent in the case of Saturn rings, in view of the results of Wisdom (1983) wherein he has shown that in asteroidal belt, 3: 1 Kirkwood gap coincides with the outer boundary of a chaotic zone.…”
mentioning
confidence: 99%